Visual communication strategy of Pecel Lele Lamongan’s advertising banner - Herwanto, Andhika Putra; Sunarto, Bambang; Pujiyanto, Pujiyanto (Fakultas Sastra Universitas Negeri Malang, 2024)
Warung Pecel Lele Lamongan is one of the SMEs that operates in the culinary sub-sector which are spread almost in every city in Indonesia. These food vendors uses an advertising banner as their information and promotion medium. This research was qualitative with qualitative data interpretation analysis through formal and communication approach. Art forms are analyzed through formalism by inspecting the elements that became a part of the subjects, such as visual elements like color, lines, shapes, textures, and visual principles such as unity and balance. Approach to communication used is to identify the visual communication strategies utilized by the advertising banners. This research shows that the visual elements and principles on Warung Pecel Lele advertising banners is a communication media that have been remembered by people and acts as a unique flagship for Pecel Lele Lamongan.Komunikasi visual iklan spanduk Pecel Lele LamonganWarung Pecel Lele Lamongan merupakan salah satu UMKM sub sektor kuliner yang tersebar hampir di seluruh kota di Indonesia. Warung ini menggunakan iklan spanduk sebagai media informasi dan promosinya. Penelitian ini menggunakan metode kualitatif, analisis data dilakukan dengan interpretasi analisis data kualitatif dengan pendekatan formal dan komunikasi. Pendekatan pada bentuk karya seni menggunakan analisis formal dengan cara memperhatikan elemen yang menjadi bentuk subjek, seperti unsur rupa yakni warna, garis, bentuk, tekstur dan prinsip rupa seperti unity dan keseimbangan. Pendekatan komunikasi digunakan untuk mengenali strategi komunikasi visual yang ada pada iklan spanduk. Hasil penelitian menunjukkan bahwa penggunaan media spanduk dan peranan unsur dan prinsip rupa pada iklan spanduk warung pecel lele merupakan sarana komunikasi visual yang melekat pada benak khalayak luas dan menciptakan citra tersendiri bagi pecel lele Lamongan.